2020
DOI: 10.1002/joa3.12444
|View full text |Cite
|
Sign up to set email alerts
|

Atrial conduction explains the occurrence of the P‐wave dispersion phenomenon, but weakly

Abstract: Background P‐wave dispersion (PWD) is believed to be caused by inhomogeneous atrial conduction. This statement, however, is based on limited little solid evidence. The aim of this study was to determine the relationship between atrial conduction and PWD by means of invasive electrophysiological studies. Methods Cross‐sectional study in 153 patients with accessory pathways and atrioventricular node reentry tachycardia (AVNRT) undergoing an electrophysiological study. Different atrial conduction times were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…Correlation was best for P-DCS and DCS-PCS, supporting the hypothesis of our research, namely, that these variables better characterize left atrial conduc-tion. Similar correlations have been reported for PMax and P-wave dispersion in other studies [16]. In a casecontrol study, Liu et al [6] found that PMax had a longer duration in subjects with paroxysmal AF than in those without.…”
Section: Discussionsupporting
confidence: 81%
“…Correlation was best for P-DCS and DCS-PCS, supporting the hypothesis of our research, namely, that these variables better characterize left atrial conduc-tion. Similar correlations have been reported for PMax and P-wave dispersion in other studies [16]. In a casecontrol study, Liu et al [6] found that PMax had a longer duration in subjects with paroxysmal AF than in those without.…”
Section: Discussionsupporting
confidence: 81%
“…All evidence points to vector theory as the main mechanism for producing PWD, On the other hand, conduction theory can explain the phenomenon but only weakly. 3,5 PWD appears as a consequence of the standardization of the 12-lead electrocardiogram (25 mm/s -10 mm/mV or 50 mm/s -20 mm/mV) and disappear when using magnification software. 3 Why does PWD continue to be a predictor parameter in clinical studies?…”
Section: P-wave Dispersion Is a Vectorial Phenomenon: Is It Time To C...mentioning
confidence: 99%
“…The vectorial justification of the PWD advise against it as a useful parameter for clinical use. 3 , 5 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Se ha realizado una evaluación clínica exhaustiva de la dispersión de la onda P en la evaluación del riesgo de fibrilación auricular en pacientes sin cardiopatía orgánica, en pacientes con hipertensión arterial, en pacientes con enfermedad de las arterias coronarias, en pacientes sometidos a cirugía de derivación coronaria, en pacientes con cardiopatías congénitas, así como en otros grupos de pacientes que padecen diversas enfermedades cardíacas o no cardíacas (29)(30)(31)(32)(33) . En consecuencia, la DP puede ser de extrema utilidad para discriminar a los pacientes con diferentes tipos de enfermedades que son propensos a desarrollar FA paroxística en el transcurso de sus vidas (34)(35)(36)(37)(38)(39)(40) .…”
Section: Mediciones Y Cálculos De La Onda Punclassified